COX-2 Inhibition in Glioblastoma Cells Counteracts Resistance to Temozolomide by Inducing Oxidative Stress - Francesca Rosaria Augello; Francesca Lombardi; Valeria Ciummo; Alessia Ciafarone; Maria Grazia Cifone; Benedetta Cinque; Paola Palumbo (Antioxidants)
Oxidative stress critically influences the pathophysiology of glioblastoma (GBM), a deadly and aggressive brain tumor. Reactive oxygen species (ROS) regulate cancer cell homeostasis, influencing the treatment response. The transcription factor Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2) activates antioxidant defenses, protecting GBM cells from therapy-induced oxidative stress and contributing to Temozolomide (TMZ) resistance. Cyclooxygenase-2 (COX-2) plays a key role in GBM chemoresistance by modulating the tumor microenvironment and supporting a pro-survival phenotype. The impact of COX-2 inhibition by celecoxib (CXB), a selective COX-2 inhibitor, combined with TMZ on oxidative stress modulation linked to resistance was investigated in GBM primary cultures and cell lines. The drug combination CXB+TMZ was tested on TMZ-sensitive and -resistant cells, and ROS levels and Nrf2 activation were evaluated via a DCFH-DA probe and Western blotting, respectively. The oxidative stress marker malondialdehyde and antioxidant enzymes were assayed using standard methods. COX-2 inhibition combined with TMZ significantly increased ROS, while TMZ alone induced a compensatory antioxidant response, sustaining resistance. Drug combination reduced this response, restoring oxidative stress even in TMZ-resistant cells. Prostaglandin E2 reversed these effects, confirming the role of the COX-2/PGE2 axis in redox balance. Drug combination increased ROS, disrupted redox homeostasis and overcame TMZ resistance, supporting COX-2 inhibition as a promising GBM therapy strategy.